2010
DOI: 10.1590/s1678-77572010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association between lactotransferrin (LTF) gene polymorphism and dental caries

Abstract: ObjectiveThe present study evaluated the association between lactotransferrin (LTF) gene polymorphism (exon 2, A/G, Lys/Arg) and dental caries.Material and MethodsA convenience sample of 110 individuals, 12 years old, was divided into: group 1, 48 individuals without caries experience (DMFT=0), and group 2, 62 subjects with caries experience (DMFT≥1). DNA was obtained from a mouthwash with 3% glucose solution, followed by a scrapping of the oral mucosa. After DNA purification, polymerase chain reaction (PCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
71
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 25 publications
(42 reference statements)
1
71
1
Order By: Relevance
“…One of the unspecific immunological factors (innate) is antimicrobial proteins: lysozyme, lactoperoxidase system, lactoferrin, high weight molecular glycoproteins and other salivary components that can act as bacterial aglutinines (2)(3)(4). Innate human salivary defense proteins such as lysozyme, lactoferrin and peroxidase are known to exert a wide antimicrobial activity against a number of bacterial, viral and fungal pathogens in vitro (1).…”
Section: Introductionmentioning
confidence: 99%
“…One of the unspecific immunological factors (innate) is antimicrobial proteins: lysozyme, lactoperoxidase system, lactoferrin, high weight molecular glycoproteins and other salivary components that can act as bacterial aglutinines (2)(3)(4). Innate human salivary defense proteins such as lysozyme, lactoferrin and peroxidase are known to exert a wide antimicrobial activity against a number of bacterial, viral and fungal pathogens in vitro (1).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, subjects were assessed for caries, and genetic studies were done to determine their LTF variant genotypes. It was shown that subjects with the lysine LTF variant had significantly less caries, and it was suggested that the lysine variant had a protective effect against caries in this genetic association study (12). While the data were loosely connected, neither of the above-cited studies (11,12) conclusively proved a direct functional link between the lysine variant in human saliva and (i) a preferential activity of this saliva against S. mutans and other acid-producing/caries-associated bacteria or (ii) reduced caries levels in humans homozygous for this lysine variant.…”
mentioning
confidence: 57%
“…It was shown that subjects with the lysine LTF variant had significantly less caries, and it was suggested that the lysine variant had a protective effect against caries in this genetic association study (12). While the data were loosely connected, neither of the above-cited studies (11,12) conclusively proved a direct functional link between the lysine variant in human saliva and (i) a preferential activity of this saliva against S. mutans and other acid-producing/caries-associated bacteria or (ii) reduced caries levels in humans homozygous for this lysine variant. This is the first report to isolate, identify, and characterize LTF in human saliva as a major protein with anti-S. mutans activity and to demonstrate that saliva containing this lysine variant protein displays antimicrobial activity against S. mutans and a host of other acid-producing oral bacteria.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…LTF is a member of the transferrin family that has roles in the innate immune response and is involved in anti-inflammatory, anti-tumor and anti-microbial activity (2)(3)(4)(5)(6)(7)(8)(9). The LTF gene is polymorphic, and several common alleles occur in the general population (3,(7)(8)(9). Alterations in the LTF gene in cells are associated with an increased incidence of cancer (10).…”
Section: Introductionmentioning
confidence: 99%